Should Malaysian Muslim women undergo egg freezing overseas? - Muhsin, Sayyed Mohamed; Che Mohamad, Che Anuar; Chin, Alexis Heng Boon (Galen Centre for Health & Social Policy, 2023)
The stresses and complications of modern living have led to an increasing trend of late marriages and delayed motherhood worldwide. This, in turn, has motivated many single women to preserve their fertility by elective egg freezing for non-medical reasons, commonly referred to as social egg freezing.